THEORETICAL AND METHODOLOGICAL FOUNDATIONS FOR THE DEVELOPMENT OF REGIONAL AGRI-FOOD MARKETS AND THE MANAGEMENT OF THEIR COMPETITIVENESS - Gyatov,; Mambetov,; Marzhokhova,; Bagova,; Shardanov , (Revista Inclusiones, 2020)
The main goal of the presented research is to study and analyze the theoretical and methodological aspects of the functioning and development of the agri-food market, its competitiveness, which is relevant in the context of globalization and growing contradictions of the national economic systems of states